Civil Law Responsibility in Artificial Intelligence-Driven Decision Making - Pelupessy, Eddy (PT. Hafasy Dwi Nawasena, 2026)
The use of artificial intelligence (AI) in legal, economic, and social decision-making has created significant legal implications in the realm of civil law. The shift from human-based decisions to autonomous algorithmic decisions raises the question of who should be held responsible when AI decisions cause harm. In the context of Indonesian law, this issue is increasingly complex because the civil legal framework still relies on the paradigm of fault-based liability as formulated in Article 1365 of the Civil Code, while AI is not recognized as a legal subject. This study aims to examine the normative framework for regulating artificial intelligence in the Indonesian legal system and analyze the construction of civil legal liability for AI-based decision-making. The research method used is normative legal research with a limited statutory, conceptual, and comparative approach. The results show that Indonesian positive law still experiences a normative vacuum in regulating accountability, standards of responsibility, and protection mechanisms for victims of AI decisions. This study confirms that the application of the concept of fault-based unlawful acts is difficult to implement effectively due to the autonomous and non-transparent nature of AI. Therefore, this study recommends the reconstruction of civil legal responsibility through the application of strict liability and risk-based liability, mapping the chain of responsibility, and strengthening the principle of prudence and victim protection to realize legal certainty and substantive justice in the era of artificial intelligence.